2013
DOI: 10.1161/hypertensionaha.111.199836
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus of the Solitary Tract (Pro)Renin Receptor-Mediated Antihypertensive Effect Involves Nuclear Factor-κB-Cytokine Signaling in the Spontaneously Hypertensive Rat

Abstract: 622( P ro)renin receptor (PRR) is highly expressed in many tissues, including those of the heart and brain, 1,2 and plays an important role in the maintenance of cardiovascular homeostasis in the periphery. 3,4 However, the role of PRR in the brain remains poorly understood. Despite intrinsically low renin concentrations in the brain, the ability of renin to signal in a similar manner to angiotensin (Ang)-II, 5 coupled with the presence of PRR in the brain cardioregulatory areas, 2,6 suggests a role for PRR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…Multiple factors affect sympathetic outflow such as sodium, ANG II, glutamate, cytokines, oxidative stress, and nitric oxide (NO) (11,12,34,41,47). Previous studies have demonstrated that brain PRR activation can increase the production of inflammatory cytokines, oxidative stress, and ANG II (32,37,46). Based on these observations, we speculate that activation of PVN PRR may be involved in increased sympathetic outflow.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…Multiple factors affect sympathetic outflow such as sodium, ANG II, glutamate, cytokines, oxidative stress, and nitric oxide (NO) (11,12,34,41,47). Previous studies have demonstrated that brain PRR activation can increase the production of inflammatory cytokines, oxidative stress, and ANG II (32,37,46). Based on these observations, we speculate that activation of PVN PRR may be involved in increased sympathetic outflow.…”
mentioning
confidence: 61%
“…Therefore, it is possible that sympathoexcitation elicited by activation of PRR in the PVN might not be sufficient to elevate ABP in normotensive animals. It would be expected that microinjection of prorenin into the PVN of hypertensive animals could induce sympathoexcitation and presser responses in a greater degree since their PRR expression is upregulated (22,38,46). Whether upregulation of PRR expression in hypertensive animals is able to enhance sympathoexcitation and induce a pressor response remains to be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations